Tracheotomia przezskórna pod kontrolą ultrasonografii - Plata, Piotr; Gaszyński, Tomasz (Anestezjologia Intensywna Terapia, 2019)
Point-of-care ultrasound in the intensive care unit has emerged as a routine bedside diagnostic tool. This article provides literature review on the ultrasound-guided percutaneous dilational tracheostomy (US-PDT), which is a relatively novel technique. US-PDT reduces periprocedural complication rate, facilitates identification of proper tube insertion site and provides other additional safety-measures versus non-ultrasound Seldinger-based PDT technique.